The characterisation of an alkali-stable maltogenic amylase from bacillus lehensis G1 and improved malto-oligosaccharide production by hydrolysis suppression - Abdul Manas, Nor Hasmaliana (Public Library Science, 2014)
A maltogenic amylase (MAG1) from alkaliphilic Bacillus lehensis G1 was cloned, expressed in Escherichia coli, purified and characterised for its hydrolysis and transglycosylation properties. The enzyme exhibited high stability at pH values from 7.0 to 10.0. The hydrolysis of beta-cyclodextrin (beta-CD) produced malto-oligosaccharides of various lengths. In addition to hydrolysis, MAG1 also demonstrated transglycosylation activity for the synthesis of longer malto-oligosaccharides. The thermodynamic equilibrium of the multiple reactions was shifted towards synthesis when the reaction conditions were optimised and the water activity was suppressed, which resulted in a yield of 38% transglycosylation products consisting of malto-oligosaccharides of various lengths. Thin layer chromatography and high-performance liquid chromatography analyses revealed the presence of malto-oligosaccharides with a higher degree of polymerisation than maltoheptaose, which has never been reported for other maltogenic amylases. The addition of organic solvents into the reaction further suppressed the water activity. The increase in the transglycosylation-to-hydrolysis ratio from 1.29 to 2.15 and the increased specificity toward maltopentaose production demonstrated the enhanced synthetic property of the enzyme. The high transglycosylation activity of maltogenic amylase offers a great advantage for synthesising malto-oligosaccharides and rare carbohydrates.